(untitled) (Scientific Bulletin of the MPU School for Higher Studies, 2023)
Study focused on the self-composition procedure from reception of specifics to preparation of the agenda. Objective: to analyze and highlight the importance of the initial phases of mediation and conciliation for conscious, responsible and sustainable negotiation. Methodology: bibliographic and documentary procedure, descriptive form, inductive method, qualitative approach and applied purpose. Results: The observance of these phases is a fundamental factor for the work to be developed within the scope of the Public Ministry to be effective, enabling people in conflict to be prepared to dialogue and have a mutual understanding of the real interests, needs and feelings they are experiencing. The procedure to be followed is a path of emotional inclusion of these people towards a new awareness of the problem they share. This change in perception makes room for a conscious vision regarding the involvement and participation of each person in the conflict contributory system and its resolution. All stages prior to negotiation must be considered by the mediator and conciliator, who must be able to deal technically and sensitively with any challenge, without neglecting the specific informational, reconstructive, organizing and pedagogical nature that each stage contains. Conclusion: carrying out mediation and conciliation, including compliance with the initial phases, will enable a more efficient procedure and negotiation in a more collaborative way, without charges and with a prospective vision, providing the construction of satisfactory solutions for everyone involved.